2020
DOI: 10.1111/dmcn.14540
|View full text |Cite
|
Sign up to set email alerts
|

Body maps in the infant brain: implications for neurodevelopmental disabilities

Abstract: This review and synthesis discusses recent work that has utilized brain imaging methods, such as the electroencephalogram (EEG) and magnetoencephalogram, to provide insights into the ways that the body is represented in the infant brain. One aspect of body representation concerns somatotopic maps of the body surface in somatosensory cortex. A good deal is known about the properties of these maps in adults, but there has been relatively little developmental work. Recent studies have provided new insights into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In particular, the perception of bodily signals has been pointed out as a facilitator of the use of strategies to regulate emotions and the ductile selection of the adequate behavior according to social context in neurotypical individuals [ 51 ]. The perception of body posture, kinesthesia and limb position are regarded as important factors for the regulation of psychological states in neurotypical populations [ 9 , 10 , 11 ]. It has also been proposed that inadequate proprioceptive information in neurodevelopmental disorders may generate a distorted regulation of somatic states implicated in the construction of emotional processes, provoking deficiencies in the emotional adaptation to the environment [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the perception of bodily signals has been pointed out as a facilitator of the use of strategies to regulate emotions and the ductile selection of the adequate behavior according to social context in neurotypical individuals [ 51 ]. The perception of body posture, kinesthesia and limb position are regarded as important factors for the regulation of psychological states in neurotypical populations [ 9 , 10 , 11 ]. It has also been proposed that inadequate proprioceptive information in neurodevelopmental disorders may generate a distorted regulation of somatic states implicated in the construction of emotional processes, provoking deficiencies in the emotional adaptation to the environment [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when frowning, the proprioceptive signal from facial muscles affects one’s emotional state, and makes individuals judge unpleasant stimuli as more negative [ 8 ]. Furthermore, the encoding of limb position and the creation of somatotopic maps have been related to the generation of behavior and social interactions [ 9 ]. In this sense, embodiment theories stress the role of sensory mechanisms in psychological and social processing, for example, the role of perception of body posture in bodily empathy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no conclusive findings about the exact developmental timing of the emergence of the sense of a bodily self, studies of brain responses to touch stimulation in neonates born preterm and at term have suggested that a somatotopic cortical pattern develops prenatally 29 . Studies on the ontogeny of human body perception in infants suggest that a pre‐reflective, non‐conceptual form of bodily self‐awareness, a primitive sense of self or ‘minimal self’, is already present in the first months of life 30 and that the minimal self‐development might be influenced by prenatal experiences including maternal stress, depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…An intact neural motor system is mandatory for perception-action coupling, as well as social understanding of the motor intentions, interpreted as visuo-motor resonance (Becchio and Castiello, 2012). These cognitive and somatosensory functions participate to the maturation of the body map representation already in infancy (Marshall and Meltzoff, 2020), and to reciprocal social cognition (Cook, 2016), which could not deploy without reliable sensory-motor system functioning.…”
Section: Gait Biomechanics and Brain Network Maturationmentioning
confidence: 99%